Fine-tuning of post-weaning pig microbiome structure and functionality by in-feed zinc oxide and antibiotics use - Ortiz Sanjuán, Juan M.; Manzanilla, Edgar G.; Cabrera-Rubio, Raúl; Crispie, Fiona; Cotter, Paul D.; Garrido, Juan J.; Ekhlas, Daniel; O’Neill, Lorcan; Argüello, Héctor (Frontiers in Cellular and Infection Microbiology, 2024)
Post-weaning diarrhoea (PWD) is a multifactorial disease that affects piglets after weaning, contributing to productive and economic losses. Its control includes the use of in-feed prophylactic antibiotics and therapeutic zinc oxide (ZnO), treatments that, since 2022, are no longer permitted in the European Union due to spread of antimicrobial resistance genes and pollution of soil with heavy metals. A dysbiosis in the microbiota has been suggested as a potential risk factor of PWD onset. Understanding pig’s microbiota development around weaning and its changes in response to ZnO and antibiotics is crucial to develop feasible alternatives to prophylactic and metaphylactic antimicrobial use. This study uses shotgun metagenomic sequencing to investigate the environmental and faecal microbiota on 10 farms using (Treated) or not using (ZnO-free) in-feed antibiotics and ZnO during the first 14 days post-weaning (dpw). Environmental samples from clean pens were collected at weaning day (0dpw), and faecal samples at 0, 7 and 14dpw. The analysis of data revealed that the faecal microbiota composition and its functionality was impacted by the sampling time point (microbiota maturation after weaning) but not by the farm environment. Treatment with antibiotics and ZnO showed no effects on diversity indices while the analyses of microbiota taxonomy and functional profiles revealed increased abundance of taxa and metabolic functions associated with Phascolarctobacterium succinatutens or different species of Prevotella spp. on the Treated farms, and with Megasphaera elsdenii and Escherichia coli on the ZnO-free farms. The analysis of diarrhoea samples revealed that the treatment favoured the microbiota transition or maturation from 0dpw to 14dpw in Treated farms, resembling the composition of healthy animals, when compared to diarrhoea from ZnO-free farms, which were linked in composition to 0dpw samples. Altogether, the results provide a comprehensive overview of the beneficial effects of ZnO and antibiotics in PWD in the microbiota transition after weaning, preventing the overgrowth of pathogens such as pathogenic E. coli and revealing the key aspects in microbiota maturation that antibiotics or ZnO alternatives should fulfil.